2021
DOI: 10.1039/d1ra02130c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive biosensors based on waveguide-coupled long-range surface plasmon resonance (WC-LRSPR) for enhanced fluorescence spectroscopy

Abstract: We investigated the coupling phenomenon between plasmonic resonance and waveguide modes through theoretical and experimental parametric analyses on the bimetallic waveguide-coupled long-range surface plasmon resonance (Bi-WCLRSPR) structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It was observed that while MEF resulted in predominantly isotropic emission, the usage of metal thin film and prism supported the realization of highly polarized and distinctly guided (directional) emission of fluorescence. This phenomenon that supports more than 50 percent signal collection of fluorescence due to its high directionality and background suppression is called as surface plasmon-coupled fluorescence (SPCF), where fluorophores are being utilized as radiating dipoles (8)(9)(10)(11)(12)(13)(14)(15). Subsequently, other kinds of luminophores were explored to realize surface plasmoncoupled phosphorescence (SPCP) and surface plasmon-coupled chemiluminescence (SPCC) (3,16).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that while MEF resulted in predominantly isotropic emission, the usage of metal thin film and prism supported the realization of highly polarized and distinctly guided (directional) emission of fluorescence. This phenomenon that supports more than 50 percent signal collection of fluorescence due to its high directionality and background suppression is called as surface plasmon-coupled fluorescence (SPCF), where fluorophores are being utilized as radiating dipoles (8)(9)(10)(11)(12)(13)(14)(15). Subsequently, other kinds of luminophores were explored to realize surface plasmoncoupled phosphorescence (SPCP) and surface plasmon-coupled chemiluminescence (SPCC) (3,16).…”
Section: Introductionmentioning
confidence: 99%